(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper examines the relationship between totalitarianism and the metaphysical illusions on which it rests. Phenomenological investigation is claimed to loosen the grip of totalitarian ideology by exposing its origins in the ’resurrective’ illusions that seek to overcome the impact of collective trauma. Phenomenology is thus shown to have emancipatory power.